Verbal–spatial IQ discrepancies impact brain activation associated with the resolution of cognitive conflict in children and adolescents. Issue 2 (15th February 2017) - Margolis, Amy E.; Davis, Katie S.; Pao, Lisa S.; Lewis, Amy; Yang, Xiao; Tau, Gregory; Zhao, Guihu; Wang, Zhishun; Marsh, Rachel
Abstract: Verbal–spatial discrepancies are common in healthy individuals and in those with neurodevelopmental disorders associated with cognitive control deficits including: Autism Spectrum Disorder, Non‐Verbal Learning Disability, Fragile X, 22q11 deletion, and Turner Syndrome. Previous data from healthy individuals suggest that the magnitude of the difference between verbal IQ (VIQ) and performance IQ (PIQ) scores (the VIQ>PIQ discrepancy) is associated with reduced thickness in frontal and parietal cortices (inferior frontal, anterior cingulate, inferior parietal lobule, and supramarginal gyrus) that support cognitive control. Unknown is whether the VIQ>PIQ discrepancy is associated with functional deficits in these areas in healthy or ill children and adolescents. We assessed the effects of the VIQ>PIQ discrepancy on fMRI BOLD response during the resolution of cognitive conflict in 55 healthy children and adolescents during performance of a Simon Spatial Incompatibility task. As the magnitude of the VIQ>PIQ discrepancy increased, activation of fronto‐striatal, limbic, and temporal regions decreased during conflict resolution ( p < .05, corrected). In exploratory analyses, the VIQ>PIQ discrepancy was associated with reduced functional connectivity from right inferior frontal gyrus to right thalamus and increased functional connectivity to right supramarginal gyrus ( p s < .03, uncorrected). The VIQ>PIQ discrepancy may be an important aspect of an individual's cognitive profile and likely contributes to, or is associated with, deficient cognitive control processes characteristic of many childhood disorders. Abstract : In this study, functional MRI was used to explore in healthy youth the relationship between individual differences in cognitive abilities and brain activation during the resolution of cognitive conflict on a cognitive control task. Children and adolescents with greater verbal relative to spatial abilities under‐engage fronto‐striatal and limbic regions during the resolution of conflict. These findings suggest that the verbal‐spatial discrepancy may contribute to deficient cognitive control processes, a characteristic of many childhood disorders.